The Role of Art Conservation in Preserving the Cultural Value of Seven Busts in the Plaza of the Faculty of Fine Arts, ISI Yogyakarta - Ratnaningtyas, Yohana Ari; Purwanto, Tambak Sihno (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
The seven busts in the plaza of the Faculty of Fine Arts ISI Yogyakarta are monuments honoring the contributions of the predecessors. The seven statues hold significant cultural value within the ISI Yogyakarta community and its surroundings. However, the condition of the seven statues is currently concerning because their existence is threatened by various destructive agents. If they do not receive immediate conservation treatment, it is feared that physical damage will affect the decline in the cultural value of the statues. This research aims to explore the role of art conservation in preserving the cultural value of seven busts in the Plaza of the Faculty of Fine Arts at ISI Yogyakarta. This study focuses on the seven busts in the Plaza of the Faculty of Fine Arts at ISI Yogyakarta, with considerations of relevance, cultural significance, and accessibility as the basis for object selection. Qualitative research methods were used to understand the role of art conservation in preserving the cultural value of the seven busts, with data collection through structured interviews, field observations, and literature studies. Data analysis was conducted systematically to uncover findings related to the cultural significance and the meaning of art conservation of the research objects. The results of the observation show that the physical damage occurring not only threatens the visual beauty of the statue but also has the potential to diminish the symbolic meaning possessed by each statue. The findings of this research highlight the importance of immediate conservation actions to preserve the physical form of the statues. Conservation is not only necessary to maintain the physical condition but also to preserve the cultural significance contained in the seven busts. Based on the findings of this research, strategic steps are needed regarding the preservation of the seven busts.